2020
DOI: 10.1097/dss.0000000000002344
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Medical Spas and Associated Complications: A Survey of Aesthetic Practitioners

Abstract: BACKGROUND Medical spas have experienced a recent rise in popularity. However, rules and regulations vary nationwide. Given the number of complications attributable to medical spas, questions remain about currently regulatory practices and whether they are sufficient to protect patients from harm. OBJECTIVE Our study investigated the current state of medical spas and their associated patient complications in the aesthetic field as well as the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…The available research on medical spas has grown. In terms of safety, medical spas have recently been linked to various complications and adverse events, which were believed to be due to improper training and education, device settings, and technique 10 . An increased risk of litigation has also been tied to laser surgery performed by non‐physician operators, especially in medical spa settings 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available research on medical spas has grown. In terms of safety, medical spas have recently been linked to various complications and adverse events, which were believed to be due to improper training and education, device settings, and technique 10 . An increased risk of litigation has also been tied to laser surgery performed by non‐physician operators, especially in medical spa settings 16 .…”
Section: Discussionmentioning
confidence: 99%
“…As of 2018, there were over 5400 medical spas 9 . However, they have recently been linked to various adverse outcomes 10 . Additional insights into their practice can provide information on their impact to the field and patient safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the growth of medical spas has outpaced cosmetic dermatologists, which has likely been accelerated by disparate state regulations covering their oversight. Of all cosmetic complications encountered by members of the American Society for Dermatologic Surgery (ASDS) in the past 2 years, the majority reported that 61%‐100% were attributable to medical spas 2 . These were believed to be the result of improper training and education, technique, and device settings.…”
Section: Medical Spasmentioning
confidence: 99%
“…However, procedures in medical spas may be associated with various complications and adverse events due to improper training or education, improper technique, and improper device settings 4. There needs to be greater regulation for the training of practitioners and their physician oversight in order to protect patients undergoing treatments in medical spas.Millennials represent an increasing subset of cosmetic patients.It is important to recognize the impact that social media can have on influencing younger people of this generation to pursue minimally and noninvasive cosmetic treatments 5.…”
mentioning
confidence: 99%